Reducing the Impact of Tinnitus on Children and Adolescents' Lives: A Mixed-Methods Concept Mapping Study - Susan Tegg-Quinn; Robert H. Eikelboom; Christopher G. Brennan-Jones; Syndon Barabash; Wilhelmina H. A. M. Mulders; Rebecca J. Bennett (Hindawi Limited, 2021)
Objectives. To generate a conceptual framework describing what is done to reduce the impact of chronic tinnitus on the lives of children and adolescents. Design. Views and experiences of 32 adults from two participant groups informed this concept mapping study: (i) a tinnitus group (adults who experienced tinnitus during childhood/adolescence, and primary carers of children/adolescents with tinnitus) and (ii) a clinicians' group (clinicians who provided care for children/adolescents with tinnitus). Participants produced statements describing what is done to reduce the impact of chronic tinnitus on the lives of children and adolescents who experience it. Through grouping and rating processes, they identified key concepts and inferred their associated benefit. Results. The participants generated 102 unique statements across four concepts: (1) Education, Support, and Counselling; (2) Support from Parents and Teachers; (3) Clinical Assessments and Management; and (4) Self-Management Techniques. Many statements highlighted the need for child-friendly and patient-centred care. Adults with personal experience of childhood tinnitus tended to perceive many of the statements as more beneficial than did the clinician group. Conclusions. Although many children will develop management strategies to assist them with their tinnitus, both the adults who experienced tinnitus as children and their parents valued strategies involving clinical care, knowledge, and expertise. Participants from the tinnitus group perceived a greater degree of benefit associated with strategies from all four clusters than the clinicians' group. However, both groups perceived the greatest degree of benefit as being associated with activities and strategies within the Education, Support, and Counselling and the Clinical Assessments and Management clusters. Both groups identified that recognising the occurrence of tinnitus for children and adolescents, acknowledging the potential for associated distress, and initiating clinical care provide the nexus of effective management. Addressing the concerns and needs of parents was also perceived as valuable; hence, approaching the management of tinnitus during childhood and adolescence from a family-centred care framework is recommended.